2012
DOI: 10.1007/s00395-011-0241-5
|View full text |Cite
|
Sign up to set email alerts
|

Remote cardioprotection by direct peripheral nerve stimulation and topical capsaicin is mediated by circulating humoral factors

Abstract: We have previously shown that remote ischemic preconditioning by limb ischemia (rIPC) or intra-arterial adenosine releases a dialyzable cardioprotective circulating factor(s), the release of which requires an intact neural connection to the limb and is blocked by pretreatment with S-nitroso-N-acetylpenicillamine (SNAP). Remote cardioprotection can be induced by other forms of peripheral stimulation including topical capsaicin, but the mechanisms of their signal transduction are incompletely understood. Rabbits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 28 publications
3
83
0
7
Order By: Relevance
“…37 440,441 induced activation of sensory fibers in the peripheral organ (1) activate the autonomic cardiac innervation through the central nervous system, and (2) release an as yet unidentified humoral factor (Figure 4). The activation of the peripheral sensory fibers involves activation of the PKCγ isoform.…”
Section: Cardioprotective Signal Transfer During Ricmentioning
confidence: 99%
See 1 more Smart Citation
“…37 440,441 induced activation of sensory fibers in the peripheral organ (1) activate the autonomic cardiac innervation through the central nervous system, and (2) release an as yet unidentified humoral factor (Figure 4). The activation of the peripheral sensory fibers involves activation of the PKCγ isoform.…”
Section: Cardioprotective Signal Transfer During Ricmentioning
confidence: 99%
“…432,444 Of importance, humoral transfer of protection with plasma or dialysate obtained after the peripheral preconditioning cycles to another individual or individual heart, even across species, is possible and highlights the functional importance of the humoral transfer signal. 433,440,441 The humoral transfer signal appears to be of a molecular weight <15 kDa and hydrophobic. There are data to support a role of NO, 64 stromal cell-derived factor-1α, …”
Section: Cardioprotective Signal Transfer During Ricmentioning
confidence: 99%
“…It also is a major compound of capsaicinoids (alkaloid) that are widely applied in pharmaceutical and clinical product [7]. As one of the natural products, it was reported that capsaicin has therapeutic properties currently employed as antitumor [8], anti-mutagenic [9], antioxidant compounds [7], antimicrobial [3], anticancer [10], cardio-protection [11], antiobesity [12], anti-diabetic [13], and antiinflammatory effect [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both topical capsaicin on the abdomen (via activation of C fiber afferents) and femoral nerve stimulation elicited release of the protective humoral factors in the circulation and reduced infarct size. 25,26 Denervation of afferents with pretreatment with capsaicin abolished the protective effect of remote limb postconditioning in a focal cerebral ischemia model. 19 In an in vivo study in mice, both femoral vein occlusion and sciatic and femoral transection abolished the cardioprotective effect of remote limb preconditioning, implying the requirement for both humoral and neural pathways.…”
Section: April 2013mentioning
confidence: 99%